The Reliability and Validity of the Cantonese Version of the Pain Treatment Satisfaction Scale (ChPTSS) in a Sample of Chinese Patients with Chronic Pain. Issue 12 (14th July 2015) - Wong, Wing S.; Chen, Phoon P.; Chow, Yu F.; Wong, Steven; Fielding, Richard
Abstract: Objectives: The Pain Treatment Satisfaction Scale (PTSS) was developed in a Western context for evaluating patients' satisfaction with pain treatment. Although the instrument was shown to possess good psychometric properties, its reliability and validity among ethnic Chinese has not been examined. This article reports the translation of the English‐language version of the PTSS into Traditional Chinese Cantonese (ChPTSS) and the preliminary examination of the reliability and concurrent predictive validity of the ChPTSS. Methods: A total of 201 Chinese patients with chronic pain completed the ChPTSS, the Chronic Pain Grade questionnaire, the mental health questions of the 12‐item Short Form Health Survey (SF‐12), and questions assessing sociodemographic and pain characteristics. Results: All ChPTSS scales demonstrated good internal consistency, with Cronbach's α s ranging from 0.77 to 0.90, and they all correlated with two criterion measures, mental health quality life (QoL) and pain disability, in expected directions. Results of hierarchical multiple regression models showed that the ChPTSS scales predicted concurrent mental health QoL ( F (6, 191) = 5.20, P  < 0.001) and pain disability ( F (6, 189) = 4.20, P  < 0.01). "Side Effects" emerged as the only significant independent predictor in both models (mental health QoL: std β  = −0.31, P  < 0.001; pain disability: std β  = 0.25, P  < 0.01). Conclusion: Our results offer preliminary evidence for the reliability and concurrent predictive validity of the ChPTSS, which can be applied in Cantonese speaking context.